The Role Of The Teacher In Arabic Language Learning At Mts Hidayatul Insan Palangka Raya (Behavioristic Theory Perspective) - Agustina, Nur Laila; Hunainah, Hunainah; Syarif, Ahmad (Institut Agama ISlam Negeri Palangka Raya, 2023)
The challenges of Arabic language learning in Madrasah Tsanawiah need to be studied continuously, to maximize the role of teachers in the learning process. This study examines the role of teachers in learning Arabic language subjects in class VII MTs Hidayatul Insan Palangka Raya based on the perspective of Behavioristic theory. This research is descriptive qualitative. The object of this research is the role of the teacher in learning Arabic language subjects in grade VII at MTs Hidayatul Insan Palangka Raya based on the perspective of behavioristic theory. While the subject of the research is the Arabic language teacher and informants principal, waka curriculum, peers, and students. The results of this study were obtained from observations and interviews conducted by researchers, namely the role of Arabic language teachers at MTs Hidayatul Insan Palangka Raya in line with the behavioristic perspective, in addition to being a learning resource, mediator, facilitator, classroom manager, and stimulus, demonstrator, motivator and evaluator. The teacher's role as a learning resource with a summary of the material is arranged in a hierarchy of difficulty. As for the role of a facilitator, with student readiness before participating in learning. The role of a class manager and stimulus by understanding student characteristics and analyzing initial abilities. The role of the teacher as a demonstrator by giving brief instructions. The role of the teacher as a motivator by providing reinforcing learning. The role of the teacher as an evaluator by correcting mistakes during learning.